2008
DOI: 10.1017/s0047279407001705
|View full text |Cite
|
Sign up to set email alerts
|

The Social Division of Welfare Surveillance

Abstract: Electronic surveillance has grown rapidly in recent years. Despite this, surveillance practices and their social products are yet to receive serious attention in the academic field of social policy. Extending Titmuss’ classical articulation of the social division of welfare, this article develops the notion of the social division of welfare surveillance to point to the way in which surveillance, compliance burdens and risk management unevenly operate within society. The implications for reinforcing social divi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
50
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(50 citation statements)
references
References 28 publications
0
50
0
Order By: Relevance
“…Her research found that income tax fraud and welfare fraud are similar in many ways (compliance and disclosure of personal information), yet are strikingly different in 'public attitudes, in the scope of surveillance in place to detect wrongdoing, in the processing of suspected cases, and in the sentencing of offenders' (101). Like Henman and Marston's (2008) work, this finding shows how the intersections of social divisions (class, gender, race) can profoundly impact one's chances of navigating government services. Under neoliberalism, white-collar crime and fraud is 'business as usual' (Snider 2003) and a by-product of individual and corporate freedom while those who have to resort to social assistance are potentially guilty until proven innocent.…”
Section: C) Costs Vs Savings? Surveillance and The Corporatization Omentioning
confidence: 68%
See 2 more Smart Citations
“…Her research found that income tax fraud and welfare fraud are similar in many ways (compliance and disclosure of personal information), yet are strikingly different in 'public attitudes, in the scope of surveillance in place to detect wrongdoing, in the processing of suspected cases, and in the sentencing of offenders' (101). Like Henman and Marston's (2008) work, this finding shows how the intersections of social divisions (class, gender, race) can profoundly impact one's chances of navigating government services. Under neoliberalism, white-collar crime and fraud is 'business as usual' (Snider 2003) and a by-product of individual and corporate freedom while those who have to resort to social assistance are potentially guilty until proven innocent.…”
Section: C) Costs Vs Savings? Surveillance and The Corporatization Omentioning
confidence: 68%
“…28 The auditor general report admits its lack of vigour in surveilling corporations to comply with tax regulations, 'We concluded that where corporations did not voluntarily comply with the provisions of the Ontario Corporations Tax Act, the Ministry did not have adequate policies and procedures in place to ensure that the appropriate amount of corporations tax was being declared and remitted by taxpayers in accordance with statutory requirements ' (2002, 6). 29 See Henman and Marston (2008). 30 For more information on white-collar crime, see Snider (2000;2003).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moffatt (1996) investigates how welfare agencies in the United States have historically operated as a technology of power to discipline low-income women in order to achieve increased social stability. Henman and Marston (2008) argue that surveillance unevenly impacts low income people and reinforces the social power of the privileged. Little (1994) In perhaps the most extensive work on the subject, Gilliom (2001) reports on how low-income women negotiate the surveillance in their lives as they receive welfare.…”
Section: Surveillance and Low-income Familiesmentioning
confidence: 99%
“…But it also makes visible the ways in which old and new meanings about gender, poverty and criminality fundamentally shape definitions of riskiness, and how welfare surveillance practices play out more generally. This is a point that is routinely overlooked in analyses of risk (HannahMoffat and O'Malley 2007;Henman and Marston 2008 In this paper, I first set out the governmentality approach that I employ in this article. I then turn to an examination of the emergence and consolidation of risk rationalities in the Australian social security system.…”
mentioning
confidence: 99%